Sustainability in Urban Transit: The Role of Expectancy Theory to Gain Loyalty Among Passengers of Free Bus Services in Klang Valley, Malaysia - Zakaria, Husna; Md. Rohani, Munzilah; Al Madhoun, Wesam; Md Isa, Hazwani (International Journal of Sustainable Construction Engineering and Technology, 2025)
This study investigates the impact of free bus services on passenger satisfaction, loyalty and environmental sustainability in Klang Valley. By applying the Expectancy Theory, the study explores the relationship between passenger expectations and actual service performance across various dimensions. The survey was conducted in Klang Valley among a sample of 314 regular passengers of the free bus service. Notably, while few passengers explicitly used the service for environmental reasons, all participants contributed to sustainability by reducing reliance on private vehicles, thereby lowering carbon emissions without realizing it. This highlights the environmental benefits of free bus services and their role in promoting eco-friendly urban transit. The findings revealed significant gaps between expectations and satisfaction levels, particularly in comfort (mean difference = 4.11041) and responsiveness (mean difference = 3.61529), which adversely affected passenger loyalty (mean difference = 3.37847). The Spearman’s rho coefficients indicated statistically significant correlations at the 0.01 level across all examined factors, with moderate correlations observed for responsiveness (0.420) and information accuracy (0.453). Findings suggest that by addressing these gaps and integrating passenger feedback, service providers can enhance both user satisfaction and environmental benefits. This study emphasizes the role of free bus services as a practical solution to urban transit challenges, demonstrating how Expectancy Theory offers a framework to improve passenger loyalty while advancing sustainability in rapidly urbanizing regions.